EMPLOYEE ENGAGEMENT DITINJAU DARI IKLIM ORGANISASI DAN WORK LIFE BALANCE SEBAGAI VARIABEL INTERVENING - Siska Adinda Prabowo Putri; Alice Zellawati; Padma Setasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas AKI Semarang, 2022)
This study aims to examine a relationship between organizational climate and employee engagement mediated by work life balance. The total sample used is 165 members of the Subbagrenmin Ditsamapta Polda Central Java. The sampling technique used is incidental sampling. The analysis used is multiple regression analysis. The instrument used on the employee engagement variable is based on the theory of Schaufeli and Bakker using a Likert scale, the organizational climate scale is based on the theory of Swift & Campbell, the work life balance scale is based on the theory of Fisher, Bulger & Smith. The results of this study indicate that first; there is a positive and significant relationship between organizational climate and work life balance, Second; there is a positive and significant relationship between work life balance and employee engagement, Third; there is a positive relationship between organizational climate and employee engagement, Fourth; There is a significant relationship between organizational climate and employee engagement mediated by work life balance. The implication of this research shows that to increase employee engagement, organizations need to also pay attention to the work life balance factor for their members.